Awareness of intrinsic motivation in leadership - Maximilian Freudling (Journal of Applied Leadership and Management, 2020)
Research questions: How well do leaders know what intrinsically motivates their followers? Do they understand the mechanism of intrinsic motivation? Methods: Research questions are investigated by means of primary research in the form of qualitative interviews at a German large-sized company. To analyze the interviews, a qualitative content analysis is performed on the paraphrased statements of the interviews. Results: The results indicate that leaders have a partially good knowledge of the factors of intrinsic motivation, even if not fully known. In the second part of the study, an investigation of leaders' comprehension of intrinsic motivation reveals that the factors of intrinsic motivation are not fully understood.
Keywords: 650